2010
DOI: 10.1124/jpet.110.170084
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Renal Cytoprotective Genes by Nrf2 and Its Potential Use as a Therapeutic Target to Mitigate Cisplatin-Induced Nephrotoxicity

Abstract: The use of the chemotherapeutic drug cisplatin is limited in part by nephrotoxicity. Cisplatin causes renal DNA adducts and oxidative stress in rodents. The transcription factor Nrf2 (nuclear factor E2-related factor 2) induces expression of cytoprotective genes, including Nqo1 (NADPH:quinone oxidoreductase 1), Ho-1 (heme oxygenase-1), and Gclc (glutamate cysteine ligase catalytic subunit), in response to electrophilic and oxidative stress. In the present study, plasma and kidneys from wild-type and Nrf2-null … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
111
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 44 publications
8
111
0
1
Order By: Relevance
“…CDDO-Im induces gene transcription of the Nrf2 target genes NQO1 and GCLC in the kidneys, and administration of CDDO-Im 24 to 48 h before treatment with ferric nitrilotriacetate prevents the increased serum urea nitrogen and creatinine levels associated with kidney damage (Tanaka et al, 2008). CDDO-Im also protects against cisplatin nephrotoxicity, a dose-limiting side effect frequently associated with the use of cisplatin chemotherapy, because blood urea nitrogen levels and damage to the proximal tubules are reduced in mice treated with CDDO-Im before cisplatin treatment (Aleksunes et al, 2010). As expected, renal damage is worse in Nrf2(Ϫ/Ϫ) mice challenged with either ferric nitrilotriacetate or cisplatin than in wildtype Nrf2(ϩ/ϩ) mice, and the protection against cisplatin toxicity by CDDO-Im is absent in the Nrf2-knockout mice (Aleksunes et al, 2010).…”
Section: F Renal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…CDDO-Im induces gene transcription of the Nrf2 target genes NQO1 and GCLC in the kidneys, and administration of CDDO-Im 24 to 48 h before treatment with ferric nitrilotriacetate prevents the increased serum urea nitrogen and creatinine levels associated with kidney damage (Tanaka et al, 2008). CDDO-Im also protects against cisplatin nephrotoxicity, a dose-limiting side effect frequently associated with the use of cisplatin chemotherapy, because blood urea nitrogen levels and damage to the proximal tubules are reduced in mice treated with CDDO-Im before cisplatin treatment (Aleksunes et al, 2010). As expected, renal damage is worse in Nrf2(Ϫ/Ϫ) mice challenged with either ferric nitrilotriacetate or cisplatin than in wildtype Nrf2(ϩ/ϩ) mice, and the protection against cisplatin toxicity by CDDO-Im is absent in the Nrf2-knockout mice (Aleksunes et al, 2010).…”
Section: F Renal Diseasesmentioning
confidence: 99%
“…CDDO-Im also protects against cisplatin nephrotoxicity, a dose-limiting side effect frequently associated with the use of cisplatin chemotherapy, because blood urea nitrogen levels and damage to the proximal tubules are reduced in mice treated with CDDO-Im before cisplatin treatment (Aleksunes et al, 2010). As expected, renal damage is worse in Nrf2(Ϫ/Ϫ) mice challenged with either ferric nitrilotriacetate or cisplatin than in wildtype Nrf2(ϩ/ϩ) mice, and the protection against cisplatin toxicity by CDDO-Im is absent in the Nrf2-knockout mice (Aleksunes et al, 2010). By selectively activating transcription of Nrf2 and PPAR␥ on glomerular endothelia and HO-1 in renal tubules and leukocytes, CDDO-Me improves both renal function and histopathology in a model of ischemic acute kidney injury; again, however, only when it is administered before the ischemic injury (Wu et al, 2011b).…”
Section: F Renal Diseasesmentioning
confidence: 99%
“…10,11 As the master regulator of antioxidant response and self-defense, Nrf2 transactivates a broad spectrum of molecules involved in antioxidation, detoxification, cell survival, anti-inflammatory response, and more; it has emerged as an attractive therapeutic target for disease of multiple organ systems, including the kidney. [12][13][14] The Nrf2-dependent self-protective antioxidant response is a complex and highly orchestrated cellular process that is regulated by myriad signaling pathways. In its inactive state, Nrf2 is sequestered in the cytoplasm and associated with the ubiquitin E3 ligase adapter Kelch-like epichlorohydrin-associated protein 1 (Keap1), leading to ubiquitination and proteasome degradation.…”
mentioning
confidence: 99%
“…On the basis of these analyses, we then focused on the mRNA expression levels of glutathione reductase (GSR), glucose-6-phosphate dehydrogenase (G6PD), ATP-binding cassette sub-family C member 2 (ABCC2), Aldo-keto reductase family 1 C1 (AKR1C1), and AKR1C3 from Fig. 2A because the expression of these genes is known to be regulated by a common transcription factor Nrf2 (16)(17)(18)(19)(20). We first confirmed that the levels of protein expression correlated with mRNA expression by Western blot analysis (Fig.…”
Section: Nsclc Cell Lines and The Sensitivity To Cbp501mentioning
confidence: 99%
“…2 and 3 suggest that high levels of expression of Nrf2 protein in CBP501-insensitive cell lines result in high levels of target gene expression. Western blot analyses were performed to examine the expression levels of additional known gene targets for Nrf2 (16)(17)(18)(19)(20). NAD(P)H dehydrogenase, quinine 1 (NQO1), AKR1B10, g-glutamyl cysteine synthetase modifier subunit (gGCSm), and glutathione peroxidase 1 (GPX1) each showed higher levels of expression in CBP501-insensitive cell lines (Fig.…”
Section: Nsclc Cell Lines and The Sensitivity To Cbp501mentioning
confidence: 99%